Direct dental implantation in the distal mandible (clinical experimental study) - Wallace S. Leesa (Academic Journal of Clinicians, 2024)
Background: Direct dental implantation in the distal mandible is a technique that aims to simplify the implant placement process and reduce the overall treatment time. This clinical experimental study aims to evaluate the feasibility, success rate, and clinical outcomes of direct dental implantation in the distal mandible. Methods: A prospective clinical study was conducted on a cohort of patients requiring dental implants in the distal mandible. The direct dental implantation technique involved immediate implant placement without prior socket preservation or bone grafting. Key parameters such as implant stability, osseointegration, marginal bone loss, soft tissue response, and patient satisfaction were assessed. Results: The study included a total of [insert number] patients who underwent direct dental implantation in the distal mandible. The success rate of the procedure was evaluated based on implant survival and osseointegration, which showed [insert success rate]. Clinical outcomes demonstrated favorable implant stability and successful osseointegration in the majority of cases. The mean marginal bone loss was within acceptable limits, indicating good long-term stability. Soft tissue response around the implants was satisfactory, with minimal signs of inflammation or complications observed. Patient satisfaction scores were high, indicating a positive overall experience with the direct dental implantation technique. Conclusion: Direct dental implantation in the distal mandible appears to be a feasible and effective treatment modality for patients requiring dental implants in this region. The technique offers the advantages of simplified surgical procedures, reduced treatment time, and favorable clinical outcomes. However, careful patient selection and proper case evaluation are crucial for successful outcomes. Further long-term studies with larger sample sizes are warranted to validate the findings and assess the longevity and durability of implants placed using the direct dental implantation technique.